MENINGKATKAN HASIL PEMBELAJARAN LOMPAT JAUH GAYA MENGGANTUNG MELALUI PERMAINAN - Priyanto, Aris (Departement of Sports Education, Faculty of Sport Sciences Yogyakarta State University, 2011)
AbstractThe study aims to improve the learning outcome of Long Jump Hanging Technique through the game approach among the students of SMAN (State High School) 1 Yogyakarta.This is a classroom action research, consisting of two cycles. The subjects of the research were 25 students of class XI IPS in SMAN 1 Yogyakarta. The research was conducted in the even semester of the 2009-2010 school year, starting from November up to December 2009, in SMAN 1 Yogyakarta. The data collection techniques were: (1) class observation on students’ learning in Long Jump Hanging Technique, (2) the achievement tests of Long Jump Hanging Technique, (3) class observation on teacher, (4) observation on class situation, (5) test on knowledge.The results of the study indicated that the game approach could improve the learning outcome of Long Jump Hanging Technique among the students of Class XI IPS in SMAN 1 Yogyakarta. Based on the achievement test of the first cycle, the average was 73.4. It increased compared to the achievement test before the treatment, 70.4. In the second cycle, the average of the students’ marks was 78.8, which increased compared to that of the first cycle. In the second cycle, 100% of the students reached 75, which is the minimum mastery criterion of Long Jump Hanging Technique in Penjasorkes subject in SMAN 1 Yogyakarta.Keywords: long-jump, learning game approachAbstrakPenelitian ini merupakan penelitian tindakan kelas (PTK) yang terdiri dari dua siklus. Subyek penelitian adalah siswa kelas XI IPS SMAN 1 Yogyakarta berjumlah 25 siswa. Penelitian berlangsung dari bulan Nopember sampai Desember 2010, pada semester genap tahun pelajaran 2009-2010. Instrumen yang digunakan dalam penelitian ini adalah: (1) obsevasi hasil belajar keterampilan lompat jauh gaya menggantung, (2) tes hasil prestasi lompat jauh gaya menggantung, (3) observasi kelas terhadap guru, (4) observasi terhadap situasi kelas, (5) tes pengetahuan. Hasil penelitian menunjukkan bahwa pendekatan permainan dapat meningkatkan hasil pembelajaran lompat jauh gaya menggantung pada siswa kelas X1 IPS SMAN 1 Yogyakarta. Berdasarkan data hasil tes pada siklus I rata-rata nilai siswa 73,4 meningkat dibandingkan sebelum diberikan tindakan yaitu 70,4. Pada siklus kedua rata-rata nilai siswa meningkat menjadi 78,8. Pada siklus kedua 100 % siswa dapat mencapai KKM (Kriteria Ketuntasan Minimal) yaitu 75 untuk nilai keterampilan lompat jauh gaya menggantung Penjasorkes di SMAN 1 Yogyakarta.Kata kunci: lompat jauh, pembelajaran pendekatan permainan